The Right Place at the Right Time: Seasonal Variation of Bacterial Communities in Arid Avicennia marina Soils in the Red Sea Is Specific to Its Position in the Intertidal - Thomson, Timothy; Ellis, Joanne I.; Fusi, Marco; Prinz, Natalie; Bennett-Smith, Morgan F.; Aylagas, Eva; Carvalho, Susana; Jones, Burton H. (Frontiers in Ecology and Evolution, 2022)
Mangrove forests play an important role in facilitating biogeochemical pathways and cycling acting as blue carbon sinks. These services are primarily regulated by the activity of the soil microbiome. However, there is still limited research into spatial and temporal variation patterns of bacterial community assemblages in mangrove soils. This study investigated important ecological scales of microprocesses that govern microbial communities in an arid mangrove ecosystem. Shifts in microbial community composition were influenced by fluctuations in environmental factors within the mangrove forests of the Red Sea influenced by seasonal changes in sea level. Notably, in summer microbial communities in shrub sites differed significantly from the fringe and the winter samples, with lower alpha diversity yet a higher dominance of specialized species capable of surviving in extreme conditions. The onset of dispersal limitation and heterogenous selection and the reduction of drift are likely the main forces shaping community assemblages. Specifically, in summer lower mean tidal levels eliminate tidal inundation creating a harsh high salinity and high temperature environment with no tidal connection thereby influencing the onset of dispersal limitation. An increased understanding of the spatial and temporal variation of bacterial communities is critical when assessing delivery of ecosystem services and their role in soil biogeochemical processes.